2016
DOI: 10.5897/ajb2015.15091
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial properties of friedelan-3-one from Pterocarpus santalinoides LHerit, ex Dc

Abstract: Chemical investigation of ethyl acetate leaf-extract of Pterocarpus santalinoides led to isolation of a friedelane-terpenoid. Structure elucidation was done by comparison of the Nuclear Magnetic Resonance (NMR) spectral features with literature data and was consistent with reported values for friedelan-3-one. The following microorganisms (Clinical isolates): methicillin resistant Staphylococcus aureus (MRSA), S. aureus, Corynebacterium ulcerans, Streptococcus pneumoniae, Campylobacter jejuni, Helicobacter pylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…al. 2013) derived from the leaf of Pterocarpus santalinoides showed antibacterial activity (Ichiko et. al.…”
Section: Discussionmentioning
confidence: 99%
“…al. 2013) derived from the leaf of Pterocarpus santalinoides showed antibacterial activity (Ichiko et. al.…”
Section: Discussionmentioning
confidence: 99%
“…Friedelan-3-one was found in the L_US extract. It has potential for use in cosmetics because of the reported antimicrobial activity against several pathogens, including Staphylococcus aureus (Ichiko et al, 2016), an important pathogen involved in the development of acne (Delost et al, 2016). This substance also has anti-inflammatory activity by inhibiting some inflammatory mediators, such as complement system, histamine, prostaglandins and pro-inflammatory cytokines (Antonisamy et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Lupeol (5), taraxerol (6) and friedelan-3-one ( 7) are isolated for the first time from the Guibourtia genus but were previously detected in other genera from Leguminosae (Fabaceae) family. Indeed, lupeol (5) was reported from Dalbergia hainanensis (Zhang et al, 2003), Cassia abbreviate (Mutasa & Kahn, 1995), Caesalpinia sappan (Oswal & Garg, 1993), Caesalpinia pulcherrima (Chiang et al, 2003) while friedelan-3-one (7) was reported from Caesalpinia digyna (Srinivasan et al, 2011), Pterocarpus santalinoides (Ichiko et al, 2016), and Pterocarpus erinaceus (Ouedraogo et al, 2011). Taraxerol (6) was isolated from Dalbergia hainanensis (Zhang et al, 2003) and D. spinosa (Anjaneyulu et al, 2005).…”
Section: Chemotaxonomic Significancementioning
confidence: 99%